Meningkatkan kemandirian siswa SD melalui pembelajaran metode montesorri - Aristya, Dian; Istiq'faroh, Nurul; Hendratno (CV. Kurnia Grup, 2023)
This study is to further illustrate how to increase student independence using Montessori learning modules. This study applies a type of literary study research. This study was conducted by examining other research related to how to increase the independence of elementary school students by describing, explaining and presenting related research and then drawing conclusions. The conclusions of this research are 1) the need for learning that is specifically designed to increase student independence, 2) teachers need to provide learning resources, 3) the need for collaboration between students, teachers and parents in order to achieve optimal educational goals.